Rendimiento de tres híbridos y una variedad de maíz zea mays l. en la zona Saracay - Cabrera Gordillo, Larry Johnson (2009)
In the parish Saracay of the Piñas city was investigated the behavior and performance of four hybrids of corn, appearing the following aims: 1. To evaluate the most productive hybrid under the conditions agro environmental in Saracay's zone. 2. To analyze the economic advantages of the hybrids. The genetic material that was studied consisted of three hybrids and an improved variety (Iniap), used as witness. The hybrids were: H 551, Pacific 9205, Brasilea 8501, and the variety Iniap 542. The treatments were distributed, according to the design of Blocks at random with four repetitions. The comparison of averages was realized by means of Duncan's test with a level of significance of 5 %; in the stage of the vegetative growth did not register important hurts of plagues, as the Spodoptera Frugiperda Adam Smith, nor of perforators of the stem and the ears Elasmopalpus lignosellus, but it was common the presence of aphids in the phase of the flowering as that of charitable insects, Sirphidos and fags which are not identified and adults of Crysopa sp. The tested hybrids, presented an aggressive growth, with good indexes of productivity, as number of ears for plant, size, weight of 100 grains. The Performance of the hybrids was not homogeneous when observed differences between the experimental units inside the blocks, which influenced the magnitude of the experimental mistake. In the hybrid Brasilia 8501 and in the variety Iniap 542 it was registered the best indexes grain - tusa, Superior to 5. The production of grain by hectare was lower than the performances refered in the scientific literature on the hybrids. The hybrid of the most production of grain was the Brasilia 8501. The variety Iniap 542, obtained a performance of the better grain that the hybrids H-551 and Pacific 9205.